Pengembangan model pembelajaran project based learning dalam mata kuliah kewirausahaan Departemen PJKR FIK UM - Heynoek, Febrita Paulina; Wiguno, Lokananta Teguh Hari; Kurniawan, Ari Wibowo; Ferdinal, Fajar Raya; Salamuddin, Norlena; Kanduwi, Exy (Physical Education Departement of University PGRI Jombang, 2025)
The purpose of this research is to develop a Semester Learning Plan (RPS) for the Entrepreneurship course for students of the Department of Physical Education, Health, and Recreation at the Faculty of Sports Science, State University of Malang. The method used is the R&D 4D model. The 4D model is one of the research and development models consisting of four steps: Define, Design, Develop, and Disseminate. The development results indicate that the implementation of Project-Based Learning (PBL) in the development of the Semester Learning Plan (RPS) for the Entrepreneurship course is effective in enhancing students' practical skills, particularly in creativity, problem-solving, collaboration, and management. Through this approach, students are given the opportunity to engage directly in entrepreneurship projects that integrate theory and practice, thus better preparing them to face the challenges of the business world.